Perkembangan Penelitian Akuntansi Zakat: Pendekatan Bibliometrik - Irman Firmansyah; Dede Arif Rahmani (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to map zakat accounting research on the dimensions.ai database. A bibliometric approach is used to answer this goal so that it can describe the development of science through mapping research publications. Research data was collected from 1994 to 2022 with the keyword 'zakat accounting'. For this purpose, the author uses the R-Studio device. The results found that the collection of articles consisted of 210 documents. It was found that the most relevant journal was Jurnal Ekonomi Syariah Teori dan Terapan. While the journals that have the greatest impact are the International Journal of Islamic Middle Eastern Finance and Management and the Journal of Islamic Accounting and Business Research. Meanwhile, the most relevant and productive writers are Kudhori and Nurhayati. While the writer who has the biggest impact is Zaid. The latest topics in zakat accounting articles are shodaqoh, accountability, research, quality, and development. Meanwhile, 'sodaqoh' and 'research' are topics that will still emerge in 2022 and are predicted to continue to be used for the following years. Through this bibliometric approach, issues regarding zakat accounting become easier to find out, more cost efficient, and make it easy for researchers to determine topics that are widely used.